Social life cycle performance of additive manufacturing in the healthcare industry: the orthosis and prosthesis cases - Bruno Soares; Ribeiro, Inês; Gonçalo Cardeal; Leite, M.; Carvalho, Helena (International Journal of Computer Integrated Manufacturing, 2021)
One of the most promising areas for additive manufacturing (AM) adoption is in the healthcare industry, through its ability to produce customized medical devices with personalized fit, feel and functionality. The shift from conventional manufacturing systems to AM implies several changes throughout the medical product’s life cycle phases, from workforce qualification to the relationship with customers. This study investigates the social impact of adopting AM in the medical devices industry. To this end, two case studies related to medical devices were developed: a prosthesis and an orthosis, by applying a social life cycle assessment (S-LCA) methodology. The methodology measures and compares performance and impact of developing, producing, and using the two devices produced by AM, and by conventional processes. The results show how the different stakeholders along the product life cycle stages are affected by the change in the manufacturing technology. Evidence of positive social impacts were found in the ‘Customers’, ‘Local community’ and ‘Society’ stakeholders. A negative social impact was found for the stakeholder ‘Value chain actors’. Furthermore, this study illustrates the suitability of the S-LCA methodology to pinpoint the benefits and negative impacts of AM in each case under study.